2011
DOI: 10.1016/j.jenvman.2011.01.022
|View full text |Cite
|
Sign up to set email alerts
|

Using Mediterranean shrubs for the phytoremediation of a soil impacted by pyritic wastes in Southern Spain: A field experiment

Abstract: This is the author’s version of a work that was accepted for publication in Journal of Environmental Management. Changes resulting from the publishing process, such as peer review, editing, corrections, structural formatting, and other quality control mechanisms may not be reflected in this document. Changes may have been made to this work since it was submitted for publication. A definitive version was subsequently published in Journal of Environmental Management 92.6 (2011): 1584-1590 http://dx.doi.org/10.10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(23 citation statements)
references
References 37 publications
1
22
0
Order By: Relevance
“…The diversity, abundance and species richness of faunal community containing nematodes were shown by Park et al (2011) to be reduced in soils contaminated with drainage from AMLs. Results of a study by Moreno-Jiménez et al (2011a, 2011b indicated that ecological impacts of AMLs are relatively high with risk, affecting potential receptors as soil micro-organisms, flora and fauna. According to these authors, remedial actions are necessary in AMLs to combat its negative impacts on the ecosystem.…”
Section: Impact Of Amls On Soil Healthmentioning
confidence: 99%
“…The diversity, abundance and species richness of faunal community containing nematodes were shown by Park et al (2011) to be reduced in soils contaminated with drainage from AMLs. Results of a study by Moreno-Jiménez et al (2011a, 2011b indicated that ecological impacts of AMLs are relatively high with risk, affecting potential receptors as soil micro-organisms, flora and fauna. According to these authors, remedial actions are necessary in AMLs to combat its negative impacts on the ecosystem.…”
Section: Impact Of Amls On Soil Healthmentioning
confidence: 99%
“…In the Mediterranean Basin, where coastal areas are largely affected by human overexploitation, the use of species able to tolerate heavy-metals and other abiotic stresses may represent a low-cost solution for phytoremediation in these harsh environments [10,14]. For example, T. gallica is a widespread species in coastal Mediterranean areas, showing a high adaptability to different environments and a high tolerance to heavy-metal polluted soils [1].…”
Section: Introductionmentioning
confidence: 99%
“…Retama sphaerocarpa plays an important role in the restoration of degraded areas, due to its capability to withstand dry environments, the symbiosis between its root system and nitrogen-fixing bacteria, its phytoremediation capabilities, and also its importance in some plant communities of arid and semiarid zones (Benayas et al 2002, Caravaca et al 2003, Moreno-Jiménez et al 2011). The aim of this study was to optimize nursery production of Retama sphaerocarpa (Fabaceae), an important shrub species characterized by a seed coat dormancy hindering germination, and used in the restoration of degraded arid and semi-arid areas.…”
Section: Introductionmentioning
confidence: 99%
“…Retama sphaerocarpa plays an important role in the restoration of degraded areas, due to its capability to withstand dry environments, the symbiosis between its root system and nitrogen-fixing bacteria, its phytoremediation capabilities, and also its importance in some plant communities of arid and semiarid zones (Benayas et al 2002, Caravaca et al 2003, Moreno-Jiménez et al 2011). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation